Agricultural Policies in Vietnam : Producer Support Estimates, 1986-2002 - Hoa Nguyen; Ulrike Grote (University of Bonn, Center for Development Research (ZEF), 2004)
Since 1986, Vietnam has moved from a centrally planned towards a market-oriented system through several major economic and trade reforms. First positive results of the reform process became visible in the early 1990s when poverty declined significantly. The Vietnamese agricultural sector has also experienced high growth and impressive export achievements. The country changed from a food importer to one of the major exporters worldwide. The question arises to what extent support policies contributed to this growth, especially of the agricultural sector. To answer this question, domestic and trade policies in the agricultural sector are analysed and the market price support (MPS) and producer support estimates (PSEs) are calculated. To account for the special conditions in Vietnam, adjustments for country- and commodity-specific factors like transportation costs, marketing margins and the quality difference of exportables (or importables) at the border and domestically are included. Selected agricultural commodities for MPS and PSE calculation comprise rice, coffee, tea, rubber, pepper, sugar, groundnut, cashew nut and pig meat. Their shares in total output exceed 70% allowing for a generalization of the calculated PSEs, thus roughly representing the whole agricultural sector. The finding is that most agricultural products were taxed in the mid 1980s until the mid 1990s. This was mainly due to the dominance and monopoly position of the state-owned sector, restrictive trade policies like import and export quotas and licenses, and distorted markets and prices in the country. The domestic reform process and the opening of the economy since the early 1990s, however, impacted on the gaps between the domestic and international prices. Thus, since the mid 1990s, the net support of agriculture became positive and increased - but still reaching only rather moderate levels. This study of Vietnam is the third comprehensive review conducted within an IFPRI project on understanding and assessing domestic and trade policies in the agricultural sector in developing countries. The data are meant to deliver a basis for further trade-related research to be conducted in the future. – – Seit 1986 hat sich Vietnam infolge mehrerer größerer Wirtschafts- und Handelsreformen von einem zentral geplanten hin zu einem marktorientierten System entwickelt. Die ersten positiven Ergebnisse des Reformprozesses wurden Anfang der neunziger Jahre sichtbar, als die Armutszahlen deutlich zurückgingen. Zudem verzeichnete der vietnamesische Agrarsektor ein hohes Wachstum und beeindruckende Exporterfolge. Das Land wandelte sich von einem Nahrungsmittelimporteur zu einem der größten Exporteure weltweit. Es stellt sich die Frage, inwieweit politische Stützungsmaßnahmen zu diesem Wachstum, speziell im Agrarsektor, beitrugen. Zur Beantwortung dieser Frage werden innen- und handelspolitische Maßnahmen, die auf den Agrarsektor abzielen, untersucht und die Marktpreisstützung (MPS) sowie Produzentensubventionsäquivalente (PSEs) berechnet. Um den speziellen Bedingungen in Vietnam Rechnung zu tragen, werden Anpassungen für landes- und produktspezifische Faktoren vorgenommen, z.B. für Transportkosten, Marketingmargen und die Qualitätsunterschiede der Export- oder Importprodukte an der Grenze und im Inland. Zur Berechnung der MPS und PSEs wurden folgende Agrarerzeugnisse ausgewählt: Reis, Kaffee, Tee, Kautschuk, Pfeffer, Zucker, Erdnüsse, Cashewnüsse und Schweinefleisch. Da der Anteil dieser Produkte an der Gesamtproduktion mehr als 70% beträgt, lässt sich eine Verallgemeinerung der errechneten PSEs vornehmen, welche somit den gesamten Agrarsektor repräsentieren. Das Ergebnis zeigt, dass die meisten Agrarprodukte während der achtziger bis Mitte der neunziger Jahre besteuert wurden. Dies lag im Wesentlichen an der Dominanz und Monopolstellung des staatlichen Sektors, an einer restriktiven Handelspolitik durch Import- und Exportquoten und Lizenzen sowie an verzerrten Märkten und Preisen im Land. Der inländische Reformprozess und die Öffnung der Wirtschaft Anfang der neunziger Jahre beeinflussten jedoch die Diskrepanz zwischen Inlandspreisen und internationalen Preisen. So nahm seit Mitte der neunziger Jahre die Netto-Agrarunterstützung steigende positive Werte an, die sich allerdings immer noch auf vergleichsweise niedrigem Niveau bewegten. Diese umfassende Untersuchung von Vietnam ist die dritte Studie, die innerhalb eines IFPRI-Projektes vorgenommen wurde, und zum besseren Verständnis und zur Einschätzung innen- und handelspolitischer Maßnahmen im Agrarsektor in Entwicklungsländern beitragen soll. Die Studie ist auch als Datenbasis für künftige handelsbezogene Forschung zu verstehen.
Keywords: 330; Agrarpolitik; Agrarreform; Agrarsubvention; Schätzung; Vietnam